The relationship of work stress and employee deviance: a study on employee in Syarikat Air Johor Holdings Sdn. Bhd. (SAJH) / Noor Adzlin Sarlan and Zulinda Mohamad Nasir - Sarlan, Noor Adzlin; Mohamad Nasir, Zulinda (Faculty of Business and Management, 2016)
Work stress has always been an interesting topic to be observed by both academicians and practitioners. The outcomes of work stress leads to employee deviance or counterproductive behavior at workplace. This study aims to investigate the relationship between work stress and employee deviance at Syarikat Air Johor Holdings Sdn. Bhd. (SAJH). In this study, the researcher choose to use three independent variable which are role conflict, role ambiguity and work overload and its relation to dependent variable which is employee deviance. A survey questionnaire will be distribute to 152 employees as a sample size. This research will use convenience sampling technique. The quantitative data in this research was analyzed by descriptive statistics using Statistical Package for the Social Sciences Software (SPSS) version 22.0. As a conclusion, this research helps the other researcher to explore the factor of stress and employee deviance in more detail.